A comparative analysis of the cohesion policy in the Russian Federation and in the European Union - Alexander Granberg; Alexander Pelyasov (European Regional Science Association (ERSA), 2003)
First years of the economic growth of the Russian economy on one side, and the enlargement of the European Union on the other side, create mych more similarities in the cohesion policy of both entities now than in the 1990-s. Russian Federation is experiencing the shift from the dominance of the operating transfers in the investment transfers as the equalizing tool. their relative importance is naturally increasing in the contemporary period of stable regional development. On the other hand, after the access of new countries in the EU the contrast between regions will irrevitably increase though not reaching the level of disparities between contemporary Russian regions. In the year 2001 federal program of diminishing interregional disparities was elaborated in Russia. Its methodology, principles and methods of distribution of investment transfers took into consideration European experience in this field. Both Russian Federation and the European Union use simple formula-based criteria to determine the exact regions-participants of the equalizing program. Both entities have special approach for the rules of distribution of the central investment transfers for most lagging countries. But in contrast with the Structural Funds policy of the European Union the stress in the Russian case is mainly on the support of the "hard" factors of regional development - physical infrastructure and not on the "soft" factors (quality of the human capital) and direct branches of the economic activity like agriculture as is the case in the regional policy of the European Union.
Keywords: 330